Human Visual Field and Navigational Strategies - José Antonio; Nelson Torro Alves; Jos A. da Silv (2012)
Collett et al. (1986) studied spatial navigation in gerbils by training them to find hidden food in an arena.As shown in Figure 1A, food was located between two identical landmarks.After learning acquisition, trials were done without food.When tested in the presence of only one landmark (removing procedure), the gerbils searched for food on the left and right sides of the landmark, maintaining the corresponding distance and direction from it (Figure 1B).In a second test, the distance between landmarks was increased (expanding procedure) and the gerbils searched for food in two different locations but also maintained distance and direction with regard to the landmarks (Figure 1C).Collet et al. (1986) concluded that gerbils www.intechopen.com